LA ESTRATEGIA DE LOS PAÍSES SURAMERICANOS EN EL SECTOR DE LA DEFENSA EN EL NUEVO MILENIO - Mancuso, Francesco (European Scientific Journal, ESJ, 2015)
In the last years, several reforms in the defence sector of South America have been scheduled; and in some cases, those reforms have been executed. Two important regional institutions were created: The Union of South American Nations (UNASUR) and its Defence Council (CDS). These two organizations do not have decision power yet, but in 2008 and in 2012, they faced and solved a regional crisis. In 2008, the Colombian raid against FARC’s group in Ecuadorian territory and the “coup d’etat” in Paraguay in 2012. In both cases, the CDS approved the measures of mutual trust, which represent a necessary step for future regional integration in this sector. It is important to analyse the diplomatic relations between these three countries involved in the crisis of 2008 (Colombia, Ecuador, and Venezuela). However, the main attention is dedicated to the analysis of the situation in Argentina, Brazil, and Chile. These Countries represent three different strategies in the defence sector. Argentina faces a critical situation; first of all, there are no clear strategy to develop its defence sector. Second, this country has a constant lack of funds. Third, their armed forces have very old equipment. Brazil is the economic power of the region. The country has planned a big strategy to modernize its armed forces, but it does not have sufficient funds for financing all its programs at the same time. Chile, called the Israel of South America, has a clear strategy to develop its defence sector and it has adequate funds for its acquisitions. It is the only country in the region that respects the quality standards of North Atlantic Treaty Organization (NATO).